2015
DOI: 10.1002/ccd.26065
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hospital treatments for peripheral arterial disease in the United States and association between payer status and quality of care/outcomes, 2007–2011

Abstract: In this analysis, patients with Medicare and Medicaid had more comorbid conditions at baseline when compared with private insurance/HMO cohorts, were more likely to present with advanced stages of PAD, undergo amputations, and develop in-hospital complications. These data unveil a critical gap and an opportunity for quality improvement in the elderly and those with poor socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Although insurance status has been shown to increase the likelihood of amputation in PAD in the United States,22, 33 socioeconomic deprivation is associated with lower extremity amputations in a nationalized health system like the United Kingdom 34. Studies from the VA system have shown better health outcomes for minorities with CAD, heart failure, and hospitalizations 35, 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…Although insurance status has been shown to increase the likelihood of amputation in PAD in the United States,22, 33 socioeconomic deprivation is associated with lower extremity amputations in a nationalized health system like the United Kingdom 34. Studies from the VA system have shown better health outcomes for minorities with CAD, heart failure, and hospitalizations 35, 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has suggested patients with Medicaid insurance often have significant comorbid conditions and present with advanced disease which may lead to increased complications following treatment. 15 Thus, there may be an inherent selection bias among providers to limit treatment among these patients.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Despite advances in medical management and transcatheter treatments, some patients still require surgical bypass. 400,000 coronary artery bypasses and 460,000 peripheral artery bypasses are performed each year in the U.S. (1,2) At least another 80,000 Americans receive arteriovenous fistulae or grafts for hemodialysis vascular access. (3,4) These procedures save lives or limbs.…”
Section: Introductionmentioning
confidence: 99%